The Effects of Spiritual Emotional Freedom Technique (SEFT) on Psychospiritual Comfort Level in Patients with Hepatic Cirrhosis - Emy Kurniawati (Politeknik Karya Persada Muna, 2022)
Baground: Spiritual emotional freedom technique as an alternative strategy to overcome the psychospiritual problems needs to be investigated to improve comfort in patients with hepatic cirrhosis. The purpose of this study was to determine the effects of spiritual emotional freedom technique on psychospiritual comfort level in patients with hepatic cirrhosis.Method: The design of this study was quasi-experimental, pre-post test with control group design. This research was conducted in the Internal Medicine Inpatient Room and Internal Medicine Poly Dr. Kariadi Semarang and Hospital Dr. Moewardi Surakarta with a sample of 35 respondents for the control group and intervention group taken using a consecutive sampling technique. The collected data then were analyzed using Wilcoxon signed ranks test, MannWhitney U test, and t-test.Results: The results showed that the comfort levels of patients in the intervention group increased after spiritual emotional freedom technique with a mean of 41.23 (pre test) to 52.89 (post test). The control group,levels did not increase with a mean of 41.09 (pre test) to 41.14 (post test). Statistical analysis showed that there was a significant difference in the mean value of the comfort levels between the intervention and control group with p-value = 0.001.Conclusions: This study concluded that the spiritual emotional freedom technique had a significant effect on the increased psychospiritual comfort of hepatic cirrhosis patients in the intervention group compared to the control group. The results of this study recommend that SEFT to be included in the nursing care plan for patients with level comfort problem.Keywords: Psychospiritual comfort levels, hepatic cirrhosis patients, spiritual emotional freedom technique